RELIABILITY OF THE ULNAR NERVE NEURODYNAMIC TEST IN ASYMPTOMATIC SUBJECTS - Bueno-Gracia , E; Fortún-Agud , M; Alegre-Etxepare , G; Antolín-Díez , J; De-las-Cuevas-Amillano , P; Escudero-Romero , R (Cuestiones de Fisioterapia, 2016)
Introduction: neurodynamic tests (NDTs) are a way to evaluate mechanosensitivity of the nervous system and to determine the involvement of neural tissues in the patients’ symptoms. There are few studies on the diagnostic utility of the ulnar nerve neurodynamic test (ULNT3). Objective: to assess the intra- and inter-tester reliability of the ULNT3 in asymptomatic subjects for the following variables: first appearance of symptoms range of motion, location and type of symptoms experienced during the test. Material and method: a reliability study was conducted. Twenty-eight asymptomatic subjects (56 cases) were enrolled in the study. The mean age was 27.54 ± 5.43 years. Two examiners alternatively performed the ULNT3, and another examiner recorded the results of the ULTN3. Intra and inter-tester reliability for the range of motion of first appearance of symptoms, location and type symptoms was calculated. Results: in the range of elbow extension very good intra-tester (ICC = 0.93) and moderate inter-tester (ICC = 0.58) reliability was obtained. Intra-tester reliability for symptoms at the elbow was very good (kappa = 0.79) and good (kappa = 0.88) for the 4th and 5th fingers. The inter-tester reliability was good (K = 0.6 to 0.69) for both locations. For tingling sensation, both reliabilities were perfect (kappa = 1) and for the feeling of tightness intra-tester reliability was very good (kappa = 0.86) and inter-tester reliability was good (kappa = 0.79). Conclusion: this study shows that there is intra and inter-tester reliability within the same session in performing the ULNT3 without external fixation devices on asymptomatic subjects.